If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7q + -3r + 5(r + -1q) = 0 Reorder the terms: 7q + -3r + 5(-1q + r) = 0 7q + -3r + (-1q * 5 + r * 5) = 0 7q + -3r + (-5q + 5r) = 0 Reorder the terms: 7q + -5q + -3r + 5r = 0 Combine like terms: 7q + -5q = 2q 2q + -3r + 5r = 0 Combine like terms: -3r + 5r = 2r 2q + 2r = 0 Solving 2q + 2r = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2r' to each side of the equation. 2q + 2r + -2r = 0 + -2r Combine like terms: 2r + -2r = 0 2q + 0 = 0 + -2r 2q = 0 + -2r Remove the zero: 2q = -2r Divide each side by '2'. q = -1r Simplifying q = -1r
| y=3x^2-15x-42 | | 31+6.50x=97.50 | | Xy-11=15 | | (1/7x^4)-(y-1) | | f(x)=(x+5)(x^2-4) | | Log(x+3)6=1 | | -6+12t=-24 | | log(6x+8)=1+log(x-3) | | 6t^2-12t+14=0 | | 9x^2-45+56=0 | | =3y+2y+7+y | | 0.3+0.2c=8.1 | | 6t^2-12t=14 | | 13p=201.50 | | 15g= | | g^2+5g-24=0 | | 3w^2(w+l)=w(w-2) | | 6x-22=2 | | 6x+14=-5x-8 | | -7+2x=-15 | | -17=10+2m | | H=-10t^2+20t+3 | | Sec^2x=2 | | 2(n+2)=5n+2 | | -12(1+5p)=2(8p+14)+36 | | 0.4x-4=5.6 | | 2*3/7(x-2) | | 6(1-5a)=66 | | 7k^2-2k-12=0 | | (5c^6d^2-3d^3)(-4c^5d)=0 | | 145-5x=y | | -5b-5-(-8)b= |